How do households allocate risk? - Christoph Engel; Alexandra Fedorets; Olga Gorelkina (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Individuals often have to decide to which degree of risk they want to expose others, or how much risk to accept if their choice has an externality on third parties. One typical application is a household. We run an experiment in the German Socio-Economic Panel with two members from 494 households. Participants have a good estimate of each other's risk preferences, even if not explicitly informed. They do not simply match this preference when deciding on behalf of the other household member, but shy away from exposing others to risk. We model the situation, and we find four distinct types of individuals, and two distinct types of households.
Keywords: C45; D13; D81; D91; 330; risk preference; household; reticence to expose others to risk; trade-off between individual and foreign risk preference